(untitled) (Journal of Environmental Science and Natural Resources, 2016)
A pot experiment was conducted to investigate the yield and nutrient content of tomato (Lycopersicon esculentum) as influenced by the application of vermicompost and chemical fertilizers. The experiment was laid out in a completely randomized design (CRD) with 3 replications and comprised of 8 treatments viz., T1 - control, T2 - recommended dose of NPK fertilizers (CF), T3 - vermicompost @ 5 t ha-1 (VC1), T4 - vermicompost @ 10 t ha-1 (VC2), T5 - VC1 + 50% CF, T6 - VC1 + 75% CF, T7 - VC2 + 50% CF and T8 - VC2 + 75% CF. Application of vermicompost @ 10 t ha-1 along with 50% chemical fertilizers showed the best performance for plant height, number of leaves plant-1, number of flowers branch-1, number of fruits branch-1, number of fruits plant-1, fruit size and yield of tomato. Vermicompost treated soils significantly contributed the highest contents of sugar, pH, N, P, K, Ca, Mg, S, Zn & B in tomato, influenced nutrient status of the postharvest soil and conserved more organic C, N, P, K, Ca, Mg, S, Zn & B contents over control. However, soluble solids and vitamin C content in tomato were not significantly influenced by the application of vermicompost and chemical fertilizers. Results of the study demonstrate that the combined application of vermicompost and chemical fertilizers would help to maintain the long-term soil productivity for sustainable tomato cultivation. J. Environ. Sci. & Natural Resources, 8(2): 115-122 2015